The Impact of a Lifestyle Intervention Program to Help Prevent Type 2 Diabetes in Rural Adults with Prediabetes in Southwestern Ontario - Azzi, Sarita (Université d'Ottawa / University of Ottawa, 2018)
Objective: To determine if a prediabetes lifestyle intervention program, tailored to rural adults from Southwestern Ontario, could decrease the risk of Type 2 Diabetes (T2D) development through positive lifestyle changes. Methods: Forty-nine intervention participants and 34 controls partook in the study. At baseline individuals diagnosed with prediabetes chose the lifestyle intervention group (6 sessions) or control group (1 session). Intervention participants were provided with tailored education which promoted positive lifestyle changes known to help prevent or delay the development of T2D. Results: Lifestyle changes and long-term improvement of T2D modifiable risk factors were achieved by the intervention participants from baseline to post-program, unlike their control counterparts, such as increasing their average daily intake of vegetables and fruit servings (p<0.001) and reducing their fasting glycemia (p=0.003). Conclusion: Positive lifestyle changes through this 6-month tailored community-based intervention was successful in helping many rural adults with prediabetes prevent the development of T2D
Keywords: Prediabetes; Rural Adults; Lifestyle Changes; Intervention Program